935 Physical rehabilitation approach for retaining health care workers suffering from musculoskeletal disorders. (24th April 2018) - Turato, M; Riva, MA; Belingheri, M; De Vito, G; D'Orso, MI; Latocca, R; Cesana, G
Abstract : Introduction: Healthcare professionals are known to be at high risk for work-related musculoskeletal disorders (MSDs). Physical rehabilitation may be an important approach for retaining Health Care Workers (HCWs) suffering from these disorders, especially among older workers. The aim of this study was to evaluate the results of a rehabilitation program dedicated to the employees of a large hospital in the Northern Italy. Methods: HCWs with shoulder disorders (SD) and Low Back Pain (LBP) were identified by the Occupational Health Unit and admitted to a physical rehabilitation program. Functional assessment scales were administered at the beginning and the end of the program: UCLA and Constant scale for SD and Borg scale for LBP. We applied Wilcoxon test for statistical comparisons. The level of significance adopted was 5%. Results: During a 24 months period, occupational physicians identified 123 HCWs with MSDs. Workers were mainly nurses (37.5%) and nursing assistive personnel (34.8%), with an average length of service of 28.53±8.92 years. Only 47 workers completed the rehabilitation program. The treated workers were mainly affected by LBP (n=22, 46.81%) and SD (n=20, 42.52%). After rehabilitation, significant improvements in the UCLA scale (p-value: 0.0206) were observed among the subjects affected by SD. The improvements in the Borg scale were also significant (p-value: 0.0011) among the subjects affected by LBP. Occupational physicians prescribed work restrictions in only five subjects (5.88%). Three workers with previous work restrictions were considered fully fit-for-work after treatment. The remaining subjects returned to work without any restrictions. Conclusions: A rehabilitation program appears to be a valuable approach for retaining older HCWs affected by MSDs. In our study, more than 88% of workers have positively evaluated the program. Occupational physicians may play an important role in this program, especially in the assessment of subjects with work-related problems.